Information Society and Library Evaluation Transitions in Portugal: A Meta-evaluation Model and Frameworks (1970–2013) - Pinto, Leonor Gaspar; Paula, Ochôa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
The need for greater understanding of assessment practices and models highlights a deficit of an up-to-date meta-evaluation model, whilst articulating with new phases in Information Society (IS) development. This paper aims to discuss the meta-evaluation model and frameworks that were created to explain the relations between IS transitions and the development of library performance evaluation models in Portugal (1970–2013).The research is based on a qualitative methodology supported by a combination of literature review with the construction and application of conceptual models and frameworks.The meta-evaluation model of the impact of transitions on library performance evaluation provides an adequate representation and explanation of relationships between IS transitions and library performance evaluation models. The CLPET (Categorizing Library Performance Evaluation Typologies) Matrix, as well as the relational framework that was developed proved to be useful analytical tools.This paper highlights the current transition of performance models into a more holistic performance management, clarifying that diverse uses and components of performance are strongly linked to IS dynamics. It will also enable readers to discuss the impact of meta-evaluation models as a strong instrument to support the challenges of visions, strategies and best practices shifted over time.